Association between domain-specific physical activity and triglyceride‑glucose (TyG) index among US adults: Evidence from NHANES 2007–2018 - Kai Yao (BMC Public Health)
Abstract Objectives The triglyceride-glucose (TyG) index is not only a reliable marker for insulin resistance, but also has broad applications in assessing the risk of various diseases, including cardiovascular disease, stroke, depression, and Alzheimer’s disease. The study aims to investigate the relationship between domain-specific moderate- or vigorous-intensity physical activity (MVPA) and TyG index among US adults. Methods The participants from the US National Health and Nutrition Examination Survey (NHANES) (2007–2018) were included. Different PA domains, including occupation-related MVPA (O-MVPA), transportation-related MVPA (T-MVPA), and leisure-time MVPA (LT-MVPA), were assessed by the Global Physical Activity Questionnaire. Weighted multivariable linear regression and the propensity score matching (PSM) method were used to determine the relationship between domain-specific MVPA and TyG index. Furthermore, stratified and mediation analyses were employed to assess the potential effect modifications and mediators on the association. Results A total of 12,069 participants were included. The participants had a weighted mean age of 47.43 ± 16.91 years and a weighted mean TyG index of 8.58 ± 0.67. Weighted multivariable linear regression showed that leisure-time MVPA (LT-MVPA), whether at any amount or achieving physical activity guidelines, was negatively associated with TyG index (β = -0.10, 95%CI: -0.13- -0.07, P < 0.001, and β = -0.13, 95%CI: -0.17- -0.10, P < 0.001, respectively). O-MVPA and T-MVPA were not correlated with the TyG index, even at the recommended amount (β = 0.01, 95%CI: -0.02–0.03, P = 0.59 for O-MVPA, and β = -0.02, 95%CI: -0.07–0.02, P = 0.32 for T-MVPA). After PSM, the results were still robust. Furthermore, the stratified analysis found that the correlation between LT-MVPA and TyG index was stronger in females, those with higher family incomes, and non-smokers. Finally, mediation analyses indicated a significant joint mediation effect of BMI on the relationships between LT-MVPA (≥ 150 min/week) and the TyG index, accounting for 31.48% of the total effect. Conclusions LT-MVPA was associated with a decreased TyG index in US adults, while no such association was observed with O-MVPA or T-MVPA. Specific recommendations for PA categories should be provided, especially for populations at risk of diseases linked to a high TyG index or insulin resistance.